Selection of elite rhizobia strains by biometric techniques for inoculation in cowpea and common-bean - Oliveira, Dâmiany Pádua (2021)
Plant breeding programs seek to obtain genotypes with high yield, yield stability, and wide adaptability to growing environments. The selection of genotypes of microorganisms for adoption as agricultural inoculants has a similar objective. In both cases, the genotype-environment interaction makes it difficult to select materials adapted to highly diverse edaphic and climatic conditions. However, with suitable biometric techniques, variation in the response of each genotype in the environments can be analyzed, allowing selection of those with the desired standard and type of response. For that purpose, Toler and AMMI (additive main effect and multiplicative interaction) modeling and the Annicchiarico methodology were used together with genotypes of nitrogen fixing bacteria in symbiosis with cowpea (Vigna unguiculata) and common bean (Phaseolus vulgaris) in seven and eight environments, respectively, to determine their adaptabilities and phenotypic stabilities. The response patterns of the symbiont strains for common bean were furthermore determined in four plant cultivars, which composed the 16 macroenvironmental components of the genotype(G)- cultivar(C)- edaphoclimatic environment(E) interaction (GCE interaction). This research showed that the Toler and AMMI models and the Annicchiarico method accurately estimated the effects of adaptability and phenotypic stability of nitrogen fixing bacteria symbiont strains for inoculation in cowpea and common-bean. High adaptability and the potentials of phenotypic stabilities of the genotypes INPA03-11B (of Bradyrhizobium elkanii) and UFLA03-164 (B. uaiense) for cowpea and UFLA02-127 (of Rhizobium sp.) for common bean were confirmed. They were the ones that least contributed to the interaction, with yield capacity equivalent to that from fertilization with high doses of mineral N. They have a foreseeable response and ability to benefit from positive environmental stimuli, but are little to not at all affected by environments of unfavorable quality. They exhibit characteristics idealized by soil microbiologists, by inoculant producers, and by farmers that desire satisfactory yields, with minimal oscillation (under high stability), even with low inputs. INPA03-11B has already been approved as an inoculant by the Brazilian Ministry of Agriculture (MAPA); UFLA03-164 and UFLA02-127 have potential for inclusion as inoculants approved for commercial use for cowpea and common bean, respectively. In addition to UFLA02-127, whose good performance does not depend on the environmental condition and the host cultivar, other strains of Rhizobium under the UFLA code tested have yield capacity and adaptabilities higher than those of the CIAT899 strain (of Rhizobium tropici) currently approved as an inoculant for common bean in Brazil. The results from CIAT899, however, are enhanced under more stressful conditions and when the host is the Madrepérola cultivar. This was the first time that these biometric techniques were applied for rhizobia selection in field studies. It is recommended that these biometric techniques be used simultaneously for approval of new strains.